Determinan peringkat obligasi korporasi di indonesia - Rosita, Nur; Sholichah, Mu’minatus; Santoso, Rahmat Agus (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the impact of the liquidity ratio on the investment rating of bonds, determine the impact of debt on the potential capital adequacy for the level of fixed income investment, determine the impact of total asset turnover on bonds with potential investment value, determine the impact of asset returns on bonds with potential investment value, knowing the impact of company size on the potential investment value of corporate bonds, and determine the impact of the bond's age on its possible investment rating. This type of research is included in the type of quantitative research with a causal approach. Based on the results of the ratio has an effect on the occurrence of investment grade corporate bond ratings. Asset Turnover has an effect on the occurrence of investment grade corporate bond ratings. This means that the high or low value of Total Asset Turnover can affect the bond ratings of non-financial companies. On Asset has an effect on the occurrence of investment grade corporate bond ratings. This means that the high and low Return On Assets cannot affect the bond ratings of non-financial companies.